Integrating PJBL-STEM in teaching modules: Innovation in biology learning improve critical and creative thinking - Lilis Sundari; P. Paidi; Nourma Yulita (University of Muhammadiyah Malang, 2026)
Background: Curriculum changes in Indonesia require teachers to prepare learning resources that can train students' important skills, especially critical thinking and creative thinking skills. Objectives: produce PJBL-STEM teaching module to improve the critical and creative thinking skills of phase E students on the topic of environmental pollution. Methods: Type of research is ADDIE model. The quasi-experimental nonequivalent effectiveness test. The research conducted from March 2024 to June 2025 at SHS Pleret. Research subjects were experts, teachers, and students. The students tested for effectiveness consisted of 30 control and 30 experimental. Feasibility and practicality data were collected using product assessment sheets. Effectiveness data were collected using valid and reliable essay questions. The data were analyzed using quantitative and statistics. Results: PJBL-STEM teaching module was feasible and practical to use as a learning tool. One-way MANOVA test results obtained a sig. value of 000 < 0.05, meaning that the PJBL-STEM teaching module is simultaneously effective in improving critical and creative thinking skills with a large effect of 0.234 (significant effect). Conclusion: PJBL-STEM teaching modules have a significant positive impact on the quality of learning, training students' critical and creative thinking skills.